2021
DOI: 10.7759/cureus.13116
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality Amongst Tocilizumab Administered COVID-19 Asian Indians: A Premonition Study From a Tertiary Care Centre

Abstract: Introduction Hyper-cytokinemia is a dreaded complication of severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) infection and an important predictor of mortality in coronavirus disease 2019 (COVID-19). The current evidence at best is still ambiguous for use of tocilizumab in cytokine storm in COVID-19. Moreover, the factors that are associated with beneficial response from tocilizumab are unknown in COVID-19. We aimed to study the clinical outcomes especially mortality vis-à-vis clinical and laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 30 publications
4
21
3
Order By: Relevance
“…There were more men than women in our cohort, and the percentage skewed even more in the deceased group, a common observation in COVID-19. However, in agreement with previous TCZ-cohorts of COVID-19, sex was not associated with the risk of death ( Moreno-Pérez et al, 2020 ; Morrison et al, 2020 ; Desai et al, 2021 ). On the contrary, risk death did increase with age, while literature shows contradictory results ( Moreno-Pérez et al, 2020 ; Morrison et al, 2020 ; Desai et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There were more men than women in our cohort, and the percentage skewed even more in the deceased group, a common observation in COVID-19. However, in agreement with previous TCZ-cohorts of COVID-19, sex was not associated with the risk of death ( Moreno-Pérez et al, 2020 ; Morrison et al, 2020 ; Desai et al, 2021 ). On the contrary, risk death did increase with age, while literature shows contradictory results ( Moreno-Pérez et al, 2020 ; Morrison et al, 2020 ; Desai et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the comorbidities associated with a higher hazard of death were immunosuppression and diabetes mellitus. Diabetes mellitus has been largely associated to poorer outcomes in COVID-19 patients [reviewed in ( Huang et al, 2020b )], while contradictory results have been observed in cohorts under TCZ treatment ( Moreno-Pérez et al, 2020 ; Morrison et al, 2020 ; Desai et al, 2021 ). Obesity has been related to a higher risk of death in COVID-19 patients ( Demeulemeester et al, 2021 ) and may act as a cofounder or modifier variable for this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and is associated with immunodeficiency as well as hyper inflammation, the latter manifesting as a cytokine storm [7]. COVID-19 was earlier thought to be a respiratory disease, but it has affected multiple organs [8][9][10][11].…”
Section: Sars-cov-2 Is Characterized By Hyper-cytokinemia Which Typimentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) has induced a negative effect on social, economic, and psychological well-being in addition to causing physical discomfort [ 2 ]. Hypercytokinemia, which usually appears in the second week of COVID-19 and is associated with immunodeficiency as well as hyperinflammation, also known as a cytokine storm, is a feature of SARS-CoV-2 [ 3 ]. COVID-19 was previously believed to be a pulmonary illness, but studies have shown that it also affects other tissues in the body [ 4 - 6 ].…”
Section: Introductionmentioning
confidence: 99%